Purificación y caracterización de la enzima Homocitrato sintasa de Malassezia furfur como posible blanco terapéutico para el tratamiento de infecciones fúngicas (2018)
Malassezia furfur (M. furfur) yeast species belong to the natural microbiome of humans. However, this microorganism generates chronic dermatological diseases, which affect a large part of the world population. The current alternatives to treat these pathologies present different disadvantages that diminish their effectiveness, since these generate dependence, resistance and do not completely eradicate the disease. Hence, in this study we wanted to purify and characterize the enzyme homocitrate synthase as it proves to be a possible therapeutic target for the treatment of diseases caused by this yeast, because its relevant role in the metabolism of the yeast. Thus, purification of a 30 kDa molecular weight protein was carried out by ionic affinity chromatography. In addition, it was possible to observe the behavior of the Coenzyme A concentration as a function of the substrate concentration and its variation over time. As a result of this characterization, an enzymatic activity...